Characterization of the Bio-Oil of Rapeseed Cake - Çulcuoglu, Esin; Ünay, Elif; Karaosmanoglu, Filiz; Angin, Dilek; Şensöz, Sevgi (Informa UK Limited, 2005)
Pyrolysis is the most important process in the thermal conversion processes of biomass. In this study, pyrolysis of the rapeseed cake was performed within a fixed bed reactor under static nitrogen atmosphere at 650°C pyrolysis temperature and at 15°C min −1 heating rate. The various properties of bio-oil acquired under these conditions were identified. The results of bio-oil showed the green candidate fuel.